2021
DOI: 10.1002/ecs2.3844
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐five years of tree demography in a frequently burned oak woodland: implications for savanna restoration

Abstract: Due to decades of fire suppression, much of the Upper Midwest savanna habitat has converted to oak woodland. In efforts to restore oak savanna habitat, fire has been re-introduced in many of these woodlands. A primary purpose of these burns is to kill the fire-sensitive mesophytic tree species, which had established themselves during the decades of fire suppression, reduce the number of understory trees, and preserve the larger more widely spaced oaks. It is clear from ongoing efforts that restoring oak savann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In the study reported here, due to persistent neighbour facilitation, trees survived best growing in groups. Since the frequent fires prevented any significant tree regeneration in the study area, either through sprouting or seedling recruits (Davis, 2021), the study showed that aggregated tree survival, by itself, can also be an important driver of post‐fire tree clumping. The results reported here, along with those by Lutz et al (2014) and Larson et al (2015), emphasize the importance of documenting the spatial patterns of surviving trees following fires, in addition to those from regeneration, to gain a fuller understanding of the processes creating the observed tree spatial patterns in fire‐frequent landscapes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study reported here, due to persistent neighbour facilitation, trees survived best growing in groups. Since the frequent fires prevented any significant tree regeneration in the study area, either through sprouting or seedling recruits (Davis, 2021), the study showed that aggregated tree survival, by itself, can also be an important driver of post‐fire tree clumping. The results reported here, along with those by Lutz et al (2014) and Larson et al (2015), emphasize the importance of documenting the spatial patterns of surviving trees following fires, in addition to those from regeneration, to gain a fuller understanding of the processes creating the observed tree spatial patterns in fire‐frequent landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Although growth in large Q. macrocarpa trees was not affected by conspecifics, it was negatively affected by heterospecific neighbours. This is likely due to interspecific competition with the much faster growing Q. ellipsoidalis , which grows (increase in dbh) three times faster than Q. macrocarpa (Davis, 2021). Also, at this site Q. ellipsoidalis typically grows taller than Q. macrocarpa , meaning that even large Q. macrocarpa trees can end up growing in the shade of Q. ellipsoidalis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations